The Learner in the Eyes of the Educator: Reflections on the Thought of Chiara Lubich and Janusz Korczak - Maria Teresa Siniscalco (Nicolaus Copernicus University in Toruń, 2019)
The article aims to highlight some pedagogical implications of the text of Chiara Lubich Looking at All the Flowers, putting it in dialogue with the work of Janusz Korczak. The universality inherent in Chiara Lubich's exhortation to "look at all the flowers", can be found in the exhortation of Korczak to "respect all the ages of life", as a consequence of the high consideration that he has of the child and his rights, first of which the right to respect. The depth of meaning that "looking at" assumes in this text of Chiara Lubich, where it becomes synonymous with "loving", can be found declined and deployed in pedagogical terms in the work of Korczak. The juxtaposition of some passages of the texts of these two authors reveals profound assonances in the anthropological foundations of their thought.